Pengaruh Mekanisme Good Corporate Governance terhadap Audit Delay dengan Ukuran Perusahaan Sebagai Variabel Moderasi: (Studi Empiris Pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Tahun 2020-2022) - Septiani Ade Anggreiningrum; Sofyan Hakim; Diah Wulandari (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Good Corporate Governance is the principles that direct and control the company to achieve a balance between power, responsibility, and supervision in carrying out business activities. In the context of auditing, the implementation of the Good Corporate Governance mechanism is believed to affect the speed of completion of the audit report. This study aims to examine the effect of good corporate governance mechanisms on audit delay with firm size as a moderating variable in property and real estate sector companies listed on the Stock Exchange in 2020-2022. The population of this study are property and real estate sector companies listed on the Stock Exchange from 2020-2022. The sampling technique in this study was to use purposive sampling technique with a total sample size of 26 companies. The data analysis method used is using and SEM-based Partial Least Square version 4.1.0.6. The results showed that the mechanism of good corporate governance has a significant and positive effect on audit delay. And firm size as a moderating variable has no effect on weakening or strengthening the relationship between Good Corporate Governance Mechanisms on Audit Delay.